'Not in the room, but the doctors were': an Australian story-completion study about consumer representation. (20th July 2019) - Scholz, Brett; Bocking, Julia; Hedt, Peter; Lu, Vinh N; Happell, Brenda
Abstract: Current mental health policy requires consumer involvement in all levels of health service management (i.e. planning, implementation, delivery and evaluation). However, current models often limit consumers to 'representation' roles that are criticized for silencing consumer views. This study compares understandings of consumer representatives' and health professionals' participation in decision-making processes in the mental health sector in Australia. Story completion methods were employed, with 34 participants (21 consumers, 8 health professionals and 5 people identifying both as consumer and health professional) completing a story stem about either a consumer representative or a health professional changing a committee meeting agenda. Using a thematic approach, three overarching themes were developed: how consumer representative roles remain unvalued, how such lack of value translates to not achieving co-production and how consumer representative roles can be better supported through allyship or subversion against organizational cultural norms. Findings suggest that organizational cultural norms in health settings need to be more inclusive of consumers to maximize the benefits of partnerships and fulfil policy expectations. Two methods for greater empowerment of consumers working in mental health are through allyship with non-consumer health professionals who support the goals of the consumer movement, and subversion of current practices.